Analisis Kepuasan Petani terhadap Kinerja Kelompok Tani (Suatu Kasus Pada Petani Di Desa Binong Kecamatan Binong Kabupaten Subang) - Agi Dahtiar; Anggito Abimanyu (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
The purpose of this research is to assess how satisfied farmers are with the performance of farmer groups in Binong village, Binong sub-district, and how well those groups' performance parameters match farmers' expectations. A questionnaire was employed for this research. A total of 75 participants were sampled using a proportional stratified random method. Attribute seven,